Integrating Traditional and Modern Educational Methods: An Analysis of Islamic Values in 'Aqīdatu Al-‘Awām and the Application of Problem-Based Learning - Mujahid, Mujahid; Khoirunisa Nur Fajrina (Jurnal Pendidikan Agama Islam, 2023)
Purpose – This study was directed to analyze the Islamic values contained in the Book of ‘Aqīdatu Al-‘Awām and how these values can be taught in a modern context. In this study context, we sought to understand more about the history and context of the Yellow Book formation, specifically the Book of ‘Aqīdatu Al-‘Awām, and how they have influenced and can continue to influence Muslim education and society in Indonesia. This study is essential for understanding the history and role of the Yellow Book in shaping Islamic knowledge and identity in Indonesia, as well as helping the development of effective and relevant teaching methods that maintain these values in the context of modern education. Design/methods/approach – This study has adopted an organized, structured, and systematic literature study research design, intending to explore Islamic values contained in the Book of ‘Aqīdatu Al-‘Awām, as well as offering a suitable learning model to teach it. Data was collected through documentation methods and analyzed using content analysis. Findings – The study found that the Book of ‘Aqīdatu Al-‘Awām encompasses several values of Islamic education, including the value of aqidah, akhlaq, worship education, and Islamic history. We also found that traditional learning models, such as the sorogan or bandongan model, can be enriched by the integration of Problem-Based Learning (PBL) methods, providing opportunities to think critically, engage actively in learning, and develop problem-solving skills. Research implications/limitations – Despite a significant contribution to Islamic education, this study has several limitations. For example, the subjective nature of our approach and data limitations. Therefore, further research needs to validate the effectiveness of PBL integration in the teaching of the book of ‘Aqīdatu Al-‘Awām. Originality/value – This study is unique in analyzing the educational values in the Book of ‘Aqīdatu Al-‘Awām and proposing the integration of PBL in teaching it. These findings make an important contribution to the discourse of Islamic education, by showing how traditional Islamic educational institutions can adapt to modern educational paradigms, while still maintaining their unique identity and values at the same time. Future research is suggested to validate the effectiveness of this integration and explore the balance between traditional and innovative teaching methodologies in Islamic education.